Altered microbiome of serum exosomes in patients with acute and chronic cholecystitis - Qing Zhu; Min-Xian Li; Ming-Chin Yu; Qi-Wen Ma; Ming-Jie Huang; Chun-Wei Lu; Chun-Bing Chen; Wen-Hung Chung; Chih-Jung Chang (BMC Microbiology, 2024)
Abstract Background This study aimed to investigate the differences in the microbiota composition of serum exosomes from patients with acute and chronic cholecystitis. Method Exosomes were isolated from the serum of cholecystitis patients through centrifugation and identified and characterized using transmission electron microscopy and nano-flow cytometry. Microbiota analysis was performed using 16S rRNA sequencing. Results Compared to patients with chronic cholecystitis, those with acute cholecystitis exhibited lower richness and diversity. Beta diversity analysis revealed significant differences in the microbiota composition between patients with acute and chronic cholecystitis. The relative abundance of Proteobacteria was significantly higher in exosomes from patients with acute cholecystitis, whereas Actinobacteria, Bacteroidetes, and Firmicutes were significantly more abundant in exosomes from patients with chronic cholecystitis. Furthermore, functional predictions of microbial communities using Tax4Fun analysis revealed significant differences in metabolic pathways such as amino acid metabolism, carbohydrate metabolism, and membrane transport between the two patient groups. Conclusions This study confirmed the differences in the microbiota composition within serum exosomes of patients with acute and chronic cholecystitis. Serum exosomes could serve as diagnostic indicators for distinguishing acute and chronic cholecystitis.